Hepatocellular Carcinoma: Advances in Systemic Therapy - Selene, Insija Ilyas; Ozen, Merve; Patel, Reema A. (Seminars in Interventional Radiology, 2024)
Hepatocellular carcinoma (HCC) is a prevalent primary liver cancer, representing over 90% of cases globally and ranking as the third leading cause of cancer-related death. This article reviews the evolving landscape of systemic therapies for advanced HCC, emphasizing recent advancements and their impact on patient outcomes. The advent of molecular targeted therapies has transformed HCC management, with sorafenib being the first FDA-approved molecular targeted therapy, setting a standard for a decade. However, recent breakthroughs involve the combination of atezolizumab and bevacizumab, demonstrating superior outcomes over sorafenib, leading to FDA approval in 2020. Another notable combination is tremelimumab and durvalumab, showing efficacy in a multinational phase III trial. Beyond these combinations, this article explores the role of other first-line treatments and subsequent therapies after progression. The evolving landscape of systemic therapies for HCC reflects a paradigm shift, with immunotherapy combinations emerging as key players alongside targeted therapies. This article highlights the complexity of treatment decisions, considering individual patient characteristics and disease etiology, and underscores the ongoing quest to optimize both systemic and local–regional therapies for improved long-term outcomes in HCC patients.
Keywords: HCC; systemic therapy; liver cancer; chemotherapy; interventional radiology